2012
DOI: 10.1093/treephys/tps087
|View full text |Cite
|
Sign up to set email alerts
|

Ground-level ozone differentially affects nitrogen acquisition and allocation in mature European beech (Fagus sylvatica) and Norway spruce (Picea abies) trees

Abstract: Impacts of elevated ground-level ozone (O(3)) on nitrogen (N) uptake and allocation were studied on mature European beech (Fagus sylvatica L.) and Norway spruce (Picea abies [L.] Karst.) in a forest stand, hypothesizing that: (i) chronically elevated O(3) limits nutrient uptake, and (ii) beech responds more sensitively to elevated O(3) than spruce, as previously found for juvenile trees. Tree canopies were exposed to twice-ambient O(3) concentrations (2 × O(3)) by a free-air fumigation system, with trees under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Although there was no significant difference between the two species, the extent of NUE reduction was relatively higher in the fir than that in larch. The contrasting responses to O3 may be associated with the species-specific utilization of needle N. Larch, which has a deciduous leaf habit, exhibits a higher photosynthetic capacity and recycles N in needles before shedding, whereas evergreen conifers such as Sakhalin fir generally maintain needle N for relatively long periods (Millard and Proe 1992, Matsuda et al 2002, Weigt et al 2012. Evergreen conifer species also have lower NUE values to facilitate adaptation to resource-poor environments (Reich et al 1992(Reich et al , 1995 and they could drive sites toward resource-poor conditions by producing litter that does not easily decompose (Reich et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there was no significant difference between the two species, the extent of NUE reduction was relatively higher in the fir than that in larch. The contrasting responses to O3 may be associated with the species-specific utilization of needle N. Larch, which has a deciduous leaf habit, exhibits a higher photosynthetic capacity and recycles N in needles before shedding, whereas evergreen conifers such as Sakhalin fir generally maintain needle N for relatively long periods (Millard and Proe 1992, Matsuda et al 2002, Weigt et al 2012. Evergreen conifer species also have lower NUE values to facilitate adaptation to resource-poor environments (Reich et al 1992(Reich et al , 1995 and they could drive sites toward resource-poor conditions by producing litter that does not easily decompose (Reich et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the thickness of the parenchyma cell layer is highly correlated with antioxidant capacity such as ascorbic acid-equivalent antioxidant capacity (Matyssek et al 2007(Matyssek et al , 2008. However, relatively few studies have compared O3 sensitivity between deciduous and evergreen trees based on LMA, particularly in coniferous species (Mortensen 1994, Wieser and Havranek 1996, Watanabe et al 2006, Weigt et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, a few studies have investigated nutrient concentration and uptake in plants under elevated O 3 [26][27][28][29]. These studies have shown that the responses of plant N, P, and K concentrations and uptake to elevated O 3 are more complicated than responses to elevated CO 2 [28,30].…”
Section: Introductionmentioning
confidence: 99%